АНТИМЕТАСТАТИЧНА ДІЯ ЛЕКТИНУ B. SUBTILIS IMB B-7724 НА МОДЕЛІ КАРЦИНОМИ ЛЕГЕНІ ЛЬЮЇС - Fedosova, N.I.; Symchych, T.V.; Cheremshenko, N.L.; Chumak, A.V.; Koval, E.V.; Karaman, O.M.; Voyeykova, I.M. (PH Akademperiodyka, 2023)
Aim: To study the antitumor and antimetastatic effects of B. subtilis IMV B-7724 lectin used in neoadjuvant and adjuvant settings in vivo. Materials and Methods: Studies were performed on C57Bl/6J mice; Lewis lung carcinoma (LLC) was used as an experimental tumor. В. subtilis ІМV В-7724 lectin was administered to tumor-bearing mice or to mice which underwent surgical resection of the primary tumor. The lectin was injected subcutaneously, 10 times, at a single dose of 5 or 1 mg/kg of body weight. The standard indicators of tumor growth and metastasis were evaluated. Results: Independently of the application settings, the lectin at a dose of 1 mg/kg of b.w. caused more pronounced effect than at a dose of 5 mg/kg of b.w. The administration of B. subtilis IMV B-7724 lectin to the mice with LLC in neoadjuvant setting did not cause notable antitumor effect but led to a significant decrease in the number and volume of lung metastases. The lectin administration in adjuvant setting significantly inhibited metastasis: the metastasis inhibition index reached 63.0% and 100% in the mice treated with the lectin at a dose of 5 mg/kg and 1 mg/kg respectively. The mean survival time of the treated animals significantly increased. Conclusion: A pronounced antimetastatic effect of B. subtilis IMV B-7724 lectin administered in an adjuvant setting was demonstrated.